The Development of Nursing Diagnosis Based on Indonesian Nursing Diagnosis Standard of Patient with Schizophrenia in Hospital - Rizki Fitryasari (Journal of Global Pharma Technology, 2020)
Abstract Objective: Schizophrenia is the common diagnosis for the patient in the hospital who care for mental illness and need several weeks for hospitalization. An accurate nursing diagnosis must be a part of the clinical pathway for patients in a hospital setting to deliver the effective intervention of nursing care. This study aimed to develop a nursing diagnosis based on an Indonesian nursing diagnosis Standart on patients with a diagnosis of schizophrenia in the Surabaya Menur Mental Hospital. Methods: A research and development (R&D) design was employed in this study with a descriptive approach. The sample was 98 medical records documents obtained by purposive sampling. The respondents were selected by inclusion criteria: patients with schizophrenia who had been hospitalized and had experienced a recurrence. The instrument used an observational sheet. The data were analyzed using univariate analysis. Result: The results showed that six nursing diagnoses were formulated during the implementation of nursing care. They were violent behavior (41.8%), hallucinations (36.7%), social isolation (11.2%), self-care deficits (7%), delusions (2%), and risk of suicide (1%). Conclusion: The nursing diagnoses developed based on Indonesian Nursing Diagnosis Standart which were classified as a psychological, behavioral, relational, and environmental category. The nursing diagnoses can be developed in the clinical pathway as a result of evidence-based so they can improve the quality of nursing care. Keywords: schizophrenia nursing diagnosis, clinical pathway, Indonesian Standard of Nursing Diagnosis